Design and calibration of a multi-robot work cell - Sousa, Gil Boyé de (2015)
The main objective of the work presented is the design of a robotic cell and its calibration. This robotic cell needs to be compact, flexible and collaborative. Concerning these constraints, an optimization work was performed using a numerical simulation software applied to industrial robots (V-REP). In addition to this, a calibration model was developed for this robotic cell using a single point laser measurement sensor. Two different methods were used to the calibration: one applied to define the position and orientation of the work-objects in the robotic cell and the other to determine the position and orientation of a cylindrical form.